Study of the Stature Structure of 10-12 Years Old Female Students in Selected Elementary Schools in Tehran - Leili Borimnejad; Nahid Salmanyazdi; Hamid Haghani (Iran University of Medical Sciences, 2016)
Background: One of the common problems in early adolescence is skeletal disorders which has an international dimension to the extent that structural and postural abnormalities screening programs are in schools agenda in different countries for years. This study aimed to determine skeletal structure of female students aged 10 to 12 years in Tehran. Methods: In this cross-sectional study after using cluster random sampling method, 283 students in fourth and fifth grades registered in academic year 2013-2014 were recruited. We investigated the skeletal structure of them by body analysis software, their demographic information by a questionnaires and their anthropometric characteristics by using standard scale. The obtained data were analyzed through descriptive statistical tests, the Chi-square test, and Kendall correlation coefficient using SPSS version 19. Results: About 6% of students (n=17) had no skeletal disorder and the rest suffered from at least one problem. Two students (0.7%) suffered from 7 disorders simultaneously. The highest percentage of obesity (39.7%) was seen in 12 years age group and the most frequent underweight (8.2%) was observed in 14 students in the age group of 10 years. About 1.8% of subjects (n=5) suffered from forward head disorder. Also, 5.7% of children (n=16) suffered from hallux valgus. The Chi-squared statistical analysis showed that there is a significant relationship between hallux valgus disorder and age (P=0.001). Finally, 20.1% of children suffered from flat foot and 22.6% of them had high foot arch. Conclusion: The majority of female students in Tehran suffered from at least one or two stature and skeletal abnFormalities. The timely detection of the problem can prevent the progress and complications of these disorders.